The Arbitration Clauses and the New Labor Procedure Law - Higa García, Alfonso (2016)
The following article offers a point of view about the arbitraje as an alternate resolution method for workplace conflicts, in this way, a more critical point of view can be developed about the possibility of the arbitraje usage regulated in the “Ley Procesal del Trabajo” which once again has been regulated in the “Nueva Ley Procesal del Trabajo”. For that purpose, the author analyzes the different points of view existing in the doctrine as well as the ones in the jurisprudence about the labour arbitration situation in the “Ley General de Arbitraje”, followed by this, it will be analyzed the regulation contained in the “Nueva Ley Procesal del Trabajo”.